Inovasi Peleburan Logam Yang Mudah, Efektif Dan Efisien Menggunakan Teknologi Portable Cupola - Atmoko, Prasetya Dwi; Trisnawan, Yogie Arisandi; Sultoni, Yusuf; Hidayatullah, Allief Bram (Program Kreativitas Mahasiswa - Teknologi, 2014)
In the era of technology like this, a variety of facilities and infrastructure supporting the majority of human life is made of metal materials. Metals include iron, steel, aluminum, copper and so forth. However, the technology required to recycle metal requires high temperatures. In addition to the metal required to process the huge cost. It is also the cause of scrap metal collectors can not be productive with its own scrap metal processing. The most collectors reselling scrap metal to a larger factory with a very low price. Designed and made with Cupola Portable is expected to increase the productivity of the collectors of scrap metals. Objectives to be achieved from Student Creativity Program is to design and create a cupola that is portable, simple, efficient and economical for metal processing. Then create a cupola that is portable in order to increase the sale value of the existing metal trash bins on metal collectors. Portable Cupola that will be created using the basic principles of ordinary cupola, but made smaller and simpler because it is intended for small and medium-sized metal collectors.Keywords: Cupola portable,scrap,productive,economical,efficient